Calculations of heat transfer in stagnation flow regions by using second-moment closure models in conjunction with the new general wall treatment. (5th August 2010) - Basara, B.
The general wall treatment adopted and extended in this work, was previously derived for the eddy viscosity model based on the elliptic relaxation approach. The main target is to provide the wall approach which combines the integration up to the wall with wall functions, and with that, to provide the optimum solution for any computational mesh. In this paper, such general wall treatment is further adjusted in order to be efficiently used with the Second-Moment Closure (SMC) models as well. The results show that the near-wall SMC can be efficiently used in conjunction with the general wall treatment.